Ready-to-Wear Fashion "Klakka" Feasibility Test with an Exploration of the Congklak Game as Design Inspiration - Supriyani, Supriyani; Krisnawati, Maria (Journal of Creativity Student, 2026)
Traditional games are a cultural heritage that is becoming less familiar to the younger generation, necessitating adaptive and relevant preservation media. This research developed the ready-to-wear clothing "Klakka," adapting the traditional game of congklak by representing congklak elements through cuts, decorations, motifs, and colors. This study aimed to test the feasibility of the ready-to-wear clothing "Klakka" as culture-based ready-to-wear clothing. The method used was descriptive quantitative, with the feasibility assessment processed as a percentage. Data collection used a feasibility assessment instrument assessed by three fashion expert validators. The instrument consisted of six indicators: design, size, sewing technique, aesthetics, performance, and uniqueness of the clothing. The results showed that the "Klakka" clothing achieved a feasibility score of 91%, which is classified as very feasible. These findings indicate that the application of cultural elements to ready-to-wear clothing can meet technical and aesthetic requirements and has potential for developing ent in the fashion industry targeting young consumers.